2013
DOI: 10.4068/cmj.2013.49.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Changes in18F-Fluorodeoxyglucose Uptake in the Spinal Cord in a Healthy Population on Serial Positron Emission Tomography/Computed Tomography

Abstract: We aimed to determine the changes in 18F-fluorodeoxyglucose (FDG) uptake in the spinal cord on two serial positron emission tomography/computed tomography (PET/CT) scans in a healthy population. We retrospectively enrolled healthy people who underwent PET/CT twice for cancer screening. We excluded those who had degenerative vertebral disease, neurologic disease, or a history of a vertebral operation. The standardized uptake value (SUVmax) of the spinal cord of each mid-vertebral body was obtained by drawing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
(36 reference statements)
3
11
0
Order By: Relevance
“…Strictly speaking, these data do not qualify as normative data derived from healthy volunteers. Nevertheless, Flanagan et al found good agreement with other reports on FDG uptake in the spinal cord of healthy volunteers, [4][5][6][7] implying that using disease-free cord segments as an internal reference may be reasonable. The choice of the maximum SUV for FDG uptake measurement not only is convenient but also has the advantage of reproducibility.…”
supporting
confidence: 62%
“…Strictly speaking, these data do not qualify as normative data derived from healthy volunteers. Nevertheless, Flanagan et al found good agreement with other reports on FDG uptake in the spinal cord of healthy volunteers, [4][5][6][7] implying that using disease-free cord segments as an internal reference may be reasonable. The choice of the maximum SUV for FDG uptake measurement not only is convenient but also has the advantage of reproducibility.…”
supporting
confidence: 62%
“…This can introduce uncontrollable variations in FDG-uptake and can result in a poor inter-patient reproducibility of the internal standard. In contrast, FDG-uptake in the cervical spinal cord has both little inter-patient variability, is stable over time and is not influenced by muscular activity [14,15]. The cur-rent analysis shows that the cervical spinal cord has equivalent FDG-uptake as the mediastinal blood pool.…”
Section: Discussionmentioning
confidence: 91%
“…An alternative structure located in the head and neck area that may be used as an internal standard is the cervical spinal cord. Literature reports that FDG-uptake in the cervical spinal cord has both little interpatient variability and is stable over time [14,15].…”
mentioning
confidence: 99%
“…He sought for another neurologist's opinion. On EEG, he had good baseline activity (11)(12)(13) and no epileptiform changes were seen. On whole body CT scan with contrast, it showed ventriculomegaly with leptomeningeal enhancement from cranial meninges down to the lumbosacral spine ( Figure 2).…”
Section: Figure 1 T1 Weighted Image Of Patient Wdr's Lumbosacral Spimentioning
confidence: 95%
“…A normal PET scan(A) showing normal uptake of the spine[11] as compared to patient WDR who has increased metabolic activity from the cervical to the lumbar cord (B), most intense on the cauda equina (C).…”
mentioning
confidence: 99%